Effect of a low molecular weight heparin molecule, dalteparin, on cellular apoptosis and inflammatory process in an incisional wound-healing model - AK, KORAY; ARSAN, SİNAN (SPRINGER, 2007)
Purpose. In this study we aimed to test the effect of a low molecular weight heparin molecule, namely dalteparin, on the inflammation and cellular apoptosis in an incisional wound-healing model in rats. Methods. Eighteen male Sprague-Dawley rats were randomly assigned to three groups (n = 6 for each group). Two full-thickness skin incisions were made over cervical and lumbar regions of all rats. Group 1 (sham group) received no treatment, group 2 (control group) received 0.01ml/g saline subcutaneously 12h two times daily from 0 to 10th postoperative day, and group 3 (dalteparin group): received 1IU/g dalteparin subcutaneously two times daily from 0 to 10th postoperative day. A histological evaluation was done by light microscopy. Apoptosis was detected immunohistochemically by anti-poly (ADP-ribose) polymerase p85 fragment pAb. Results. The early inflammatory response and related tissue edema were depressed on day 3 in the dalteparin group when compared with those in the other groups (P < 0.05). Fibroblast proliferation was also depressed on day 10 in the dalteparin group compared to the others (P < 0.05). Furthermore, increased apoptosis was detected in the dalteparin group both on day 3 and day 10. Conclusion. Our results showed that dalteparin may adversely affect the incisional wound healing by suppressing the early inflammatory process and increasing cellular apoptosis; however, further studies are warranted to confirm the results.
Keywords: low molecular weight heparin; wound healing; inflammatory process; apoptosis; CHRONIC FOOT ULCERS; UNFRACTIONATED HEPARIN; ANGIOGENESIS; ENOXAPARIN; ADHESION